Legal Protection In The Sale And Purchase Of Online Game Accounts Prohibited By Developers: A Normatif Study Of Mobile Legends. - Baihaqi, Muchammad Ariqul; Yudhantaka, Lintang (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of digital technology has spurred the emergence of the practice of buying and selling online game accounts, including in the game Mobile Legends. This practice is widely carried out by the public even though it is explicitly prohibited by the developer through the Terms of Service. This study aims to analyze the legal status of online game account sales and purchase transactions based on Indonesian civil law and to examine the legal remedies available to aggrieved parties. The research method employed is a normative legal approach using statutory and conceptual frameworks. The findings indicate that the buying and selling of online game accounts fall into a legal gray area because they are not explicitly regulated by law, yet they can still be analyzed through the provisions of the Indonesian Civil Code regarding contracts. On the other hand, prohibitions by developers create a conflict of norms between civil law and private contractual provisions. Legal remedies that can be pursued include litigation and non-litigation avenues, although their effectiveness remains limited. Therefore, clearer legal certainty regarding digital asset transactions in Indonesia is needed.